Analysis Of Liquidity, Solvency, And Profitability Ratios In Measuring Financial Performance At PT. Bukit Asam Tbk Indonesia - Mhd. Ridho Ermansyah Lubis; Tia Aryani Sitanggang; Devi Mayasari; Della Puspita; Nina Andriany Nasution (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to describe and analyze the financial performance of PT Bukit Asam Tbk Indonesia, which is reviewed using the analysis of liquidity, solvency, and profitability ratios. The analysis method used is the descriptive analysis method. The data used in this study is secondary data derived from the main website of PT Bukit Asam Tbk and focuses on the financial statements for the period 2018–2022. The results of the research analysis show that the company performance of PT Bukit Asam Tbk Indonesia in terms of liquidity, solvency, and profitability ratios is in the "very good" category by industry standards. However, there are only two aspects of measurement in the "less good" category of PT Bukit Asam Tbk Indonesia's financial performance in several years, namely in terms of debt-to-assets ratio and net profit margin. It can be seen that this company can increase the value of assets and capital to pay corporate debt and guarantee creditor interest payment.